2002
DOI: 10.3732/ajb.89.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum in the opal silica reticule of phytoliths: a new tool in palaeoecological studies

Abstract: X-ray microanalysis was employed to screen biogenic plant silica extracted from the aboveground tissues of 20 species (Gramineae, Cyperaceae, Ericaceae, and Coniferae) occurring in subalpine and alpine grasslands, heaths, and woodlands on siliceous bedrock in the Valaisan Swiss Alps. Among the taxa investigated, only woody species produced a high proportion of phytoliths containing aluminum in the form of aluminosilicates. This difference between the chemical composition of wood and that of herbaceous phytolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 31 publications
(44 reference statements)
1
24
0
3
Order By: Relevance
“…A key observation in this direction was made by Albert et al (2006) who reported that the soil phytolith assemblage under a certain vegetation type was significantly different from the plant phytolith assemblage from which the soil phytoliths are derived. This could be due to some morphotypes being absent in the sediments because they are less stable than other morphotypes, as has been noted previously (Alexandre et al, 1997;Carnelli et al, 2002). This is a serious concern for phytolith research in archaeology and ecology, as the archaeological and paleoecological interpretations of phytolith assemblages are essentially based on the relative abundances of the various phytolith morphotypes (Piperno, 1988).…”
Section: Introductionmentioning
confidence: 92%
“…A key observation in this direction was made by Albert et al (2006) who reported that the soil phytolith assemblage under a certain vegetation type was significantly different from the plant phytolith assemblage from which the soil phytoliths are derived. This could be due to some morphotypes being absent in the sediments because they are less stable than other morphotypes, as has been noted previously (Alexandre et al, 1997;Carnelli et al, 2002). This is a serious concern for phytolith research in archaeology and ecology, as the archaeological and paleoecological interpretations of phytolith assemblages are essentially based on the relative abundances of the various phytolith morphotypes (Piperno, 1988).…”
Section: Introductionmentioning
confidence: 92%
“…Assim como pólen e esporos, fitólitos fósseis são usados como representativos de antigas formas de vegetação nas pesquisas sobre o Quaternário. 12 Carnelli et al 13 analisaram fitólitos de monocotiledôneas, dicotiledôneas e coníferas dos Alpes suíços, detectando, a partir de análises semiquantitativas, virtual ausência de Al em fitólitos de monocotiledôneas, enquanto em fitólitos de folhas de dicotiledôneas e coníferas a presença de Al foi comum. Os autores sugerem que a variabilidade nos teores de Al entre grupos vegetais pode auxiliar na análise de assembleias de fitólitos indicadores de paleoambientes, visto que a maior resistência à dissolução de certos tipos morfológicos, que seriam diferencialmente preservados, levaria a um enriquecimento gradual destes fitólitos nos horizontes mais profundos de solos não perturbados, como observado por Alexandre et al.…”
Section: Introductionunclassified
“…Soils may have several percent of phytoliths. Wood species produce a high proportion of phytoliths containing Al (Cartelli et al, 2002). Dissolution rates of phytoliths may vary by 12 orders of magnitude, depending on coatings and Al concentration (Iler, 1973;Van Bennekom et al, 1989).…”
Section: Introductionmentioning
confidence: 99%